Examining Folk Pedagogies of Science Exhibit Designers - Kehl, Winifred (My University, 2012)
Science museum exhibits have the potential to positively impact science education, scientific literacy, public engagement with science and interest in the STEM fields. The personal exhibit design philosophies or "lay theories" of science exhibit designers impact how science exhibits are designed and, ultimately, what visitors gain from experiences them. In order to investigate the impact of science exhibit designers' lay theories on science exhibit design, the self-reported practices of seven science exhibit designers are mapped onto best practices from the National Association for Museum Exhibition and cognitive science research summarized by the National Research Council. The results suggest that a more rigorous investigation of what resources science exhibit designers use and how they use them as well as the mitigating effects of institutional management may be important to understanding what research informs science exhibit design.
Thesis (Master's)--University of Washington, 2012
Keywords: design; exhibits; museology; public engagement with science; science; scientific literacy; Museum studies; Museology